Brás, Bexiga e Barra Funda, de Alcântara Machado: uma narrativa-registro da cidade de São Paulo - Silva, Isabel dos Santos (2010)
This work aims at proposing an analysis on Antonio de Alcântara Machado s piece Brás, Bexiga e Barra Funda (1927), considering it a register-narrative of Italian-paulistano factory-hands quotidian and the cartography of São Paulo in the 1920 s. Thereunto we chose three narrative elements that proved to be essential to the register-narrative elaboration: the author aesthetic project - (documental prose), the presence of a city s space documentarist narrator and the register of the Italian-paulistano labourers quotidian life. The opening chapter captures Alcântara Machado s point of view on the 1920 s Literature and presents the documental prose principles, a project coined and made real by the author in Brás, Bexiga e Barra Funda. The documentarist narrator is shown on the second chapter, where São Paulo s cartography is taken as a privileged fictional spot to the narrative-register documentation, as well as Italian-paulistano customs, traditions and habits. The final chapter is focused on the analysis of the short stories Gaetaninho, Lisetta and Carmela from the social-historic perspective, highlighting the Italian-paulistano workers quotidian register, captured in their drama and aspirations put in focus by oppression caused by the irreversible city modernization